(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study investigates the impact of magnetohydrodynamic force and buoyancy on convective heat and mass transfer flow along a moving vertical porous plate, considering the presence of thermal radiation and chemical reaction. The governing partial differential equations are transformed into a set of self-similar equations using similarity transformations. These resulting equations are then numerically solved employing the fourth-order Runge-Kutta method in conjunction with the shooting technique. The outcomes encompass velocity, temperature, concentration, skin-friction, Nusselt number, and Sherwood number.